Український політичний анекдот на сторінках “Щоденників. 1923–1929” Сергія Єфремова - Головецька, Н. (Народна творчість та етнографія, 2007)
The article confirms that the Ukrainian political anecdote was fully developed as a genre of authentic Ukrainian folklore during the first years of the Soviet power. It had not only entertaining and aesthetic function, but also a practical one; it retained value of events and phenomena of the Soviet reality which were not manifested in the official written sources.